Limbah Beton Sebagai Material Agregat Halus Terhadap Kuat Tekan Karakteristik - Budiman, Budiman (INTEK: Jurnal Penelitian, 2019)
Concrete waste from building construction can cause problems for the environment [1]. The use of fine aggregates from concrete waste can be a solution. The purpose of this study is to determine the value of aggregate characteristics and the value of concrete compressive strength from the utilization of concrete waste as substitution fine aggregate use the DOE (department of environment) method and referring to standards SNI. This study used 50% and 60% waste mortal substitution on sand. The results showed that the characteristics of fine aggregate and coarse aggregate met the characteristic requirements for fineness modulus sand of 2.65 (Zone 2) while the aggregate was roughly 6.44 (Zone 3). The value of compressive strength with 50% and 60% concrete waste substitution each obtained the value of characteristic compressive strength of 57.24 kg / cmÂ² and 101.03 kg / cmÂ². The value of using mortar waste as fine aggregate substitution gives a positive value to the quality of concrete. This is evidenced increase in the value of 14.89% in concrete waste substitution 60%.